Disruption of dynactin complex function in intellectual disability - Yuxiang Pan; Huijuan Li; Mingchun Liao; Tianyun Wang; Xiaoli Rao; Qiu Wang; Ping Hu; Dandan Zheng; Yang Jiao; Luonan Chen; Yun Stone Shi; Yonghua Zhao; et al. (Proceedings of the National Academy of Sciences, 2026)
Intellectual disability (ID) is a highly prevalent condition affecting approximately 200 millions of people worldwide, characterized by impaired cognitive function. Dynactin complex consists of multiple protein subunits and is required for intracellular trafficking and synaptic homeostasis in developing and mature neurons. Here, we identify deleterious variants of dynactin subunit 4 (DCTN4) in ID pedigrees. DCTN4 ablation in mice results in altered neuronal positioning and apoptosis in neural progenitor cells. Notably, mice carrying the ID-linked DCTN4 variant exhibit cognitive deficits with impaired dendritic development. Cortical neurons with DCTN4 deficiency or variant show reduced levels of various dynactin subunits, suggesting that deficits in dynactin complex affects synaptic function. Furthermore, disruption of the DCTN4–JIP3 complex impairs lysosomal transport and dendritic development as well as synaptic development. Importantly, we showed that damaging variants in another dynactin subunit DCTN2 also disrupt neuronal positioning, reinforcing the critical role of dynactin complex in neurodevelopment and ID pathogenesis. These findings illustrate dysfunctional dynactin complex as a previously unrecognized disease mechanism of ID.